The relationship of regional hemoglobin A1c testing and amputation rate among patients with diabetes. (April 2017) - Newhall, Karina A; Bekelis, Kimon; Suckow, Bjoern D; Gottlieb, Daniel J; Farber, Adrienne E; Goodney, Philip P; Skinner, Jonathan S
Objective: The risk of leg amputation among patients with diabetes has declined over the past decade, while use of preventative measures—such as hemoglobin A1c monitoring—has increased. However, the relationship between hemoglobin A1c testing and amputation risk remains unclear. Methods: We examined annual rates of hemoglobin A1c testing and major leg amputation among Medicare patients with diabetes from 2003 to 2012 across 306 hospital referral regions. We created linear regression models to study associations between hemoglobin A1c testing and lower extremity amputation. Results: From 2003 to 2012, the proportion of patients who received hemoglobin A1c testing increased 10% (74% to 84%), while their rate of lower extremity amputation decreased 50% (430 to 232/100, 000 beneficiaries). Regional hemoglobin A1c testing weakly correlated with crude amputation rate in both years (2003 R = −0.20, 2012 R = −0.21), and further weakened with adjustment for age, sex, and disability status (2003 R = −0.11, 2012 R = −0.17). In a multivariable model of 2012 amputation rates, hemoglobin A1c testing was not a significant predictor. Conclusion: Lower extremity amputation among patients with diabetes nearly halved over the past decade but only weakly correlated with hemoglobin A1c testing throughout the study period. Better metrics are needed to understand the relationship between preventative care and amputation.